Gender-Specific Effect of 5-HT and 5-HIAA on Threshold Level of Behavioral Symptoms and Sex-Bias in Prevalence of Autism Spectrum Disorder - Chakraborti, Barnali; Verma, Deepak; Guhathakurta, Subhrangshu; Jaiswal, Preeti; Singh, Asem Surindro; Sinha, Swagata; Ghosh, Saurabh; Mukhopadhyay, Kanchan; Mohanakumar, Kochupurackal P.; Rajamma, Usha (Frontiers in Neuroscience, 2020)
Platelet hyperserotonemia in ASD subsets, efficacy of SSRI in reducing behavioral deficits and gender-bias in normal serotonin synthesis suggest a disruption in stringent regulation of serotonin metabolism in ASD. Therefore, we investigated gender-specific changes in 5-HT and 5-HIAA in ASD to assess its effect on behavior of male and female subjects. ASD cases (n=215) were examined using CARS. Platelet 5-HT (104 cases and 26 controls) and platelet/plasma 5-HIAA (73 cases and 17 controls) were estimated using HPLC-ECD. In male probands, we observed increase in platelet 5-HT content in association with increase in the score for adaptive responses and increase in platelet 5-HIAA levels with concomitant decline in the score for intellectual response. Age did not influence the neurochemical parameters in them, but emotional, visual responses and activity level scores decreased with age. Conversely in female probands, plasma 5-HIAA level significantly attenuated with age, when platelet 5-HT content remained unchanged. Interestingly, platelet/plasma 5-HT and plasma 5-HIAA were higher in female controls and female probands displayed more severe autism-associated behaviors. Overall results indicate a gender-bias in the regulation of 5-HT and 5-HIAA, which probably increases the threshold level of ASD phenotypes in the females, thereby affecting ASD prevalence in a sex-specific manner.